The oral application of the Onderstepoort biological products fowl typhoid vaccine, its safety, efficacy and duration of protection in commercial laying hens - Picard, J.A. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2006.